Pemanfaatan Teknologi Informasi (Software Perpustakan) pada Sekolah - Delvalina Delvalina (Universitas Islam Negeri Imam Bonjol Padang, 2018)
In a school, the flow of borrowing and lending the books is a routine activity with a high amount of transaction. All transaction are the matter to be booked and noted. Every transaction needs noting of some information like identities of the borrowers that creates high circulation of transactions. These transactions need a well established data storage system in order to be easily and fast processed. But unfortunately, at schools there are no library application as an automatic data storage machine to ease the work of librarians and to simpler the visitors’ searching of the books. By the availability of this software, it is expected that users of this library can get the information they need.